2003
DOI: 10.1099/mic.0.26535-0
|View full text |Cite
|
Sign up to set email alerts
|

The surface (S-) layer is a virulence factor of Bacteroides forsythus

Abstract: Bacteroides forsythus has emerged as a crucial periodontal pathogen with possible implications for systemic disease. The aim of this study was to isolate the S-layer from B. forsythus and examine its virulence potential as a part of efforts to characterize virulence factors of B. forsythus. The role of the S-layer in the haemagglutinating and adherent/invasive activities was evaluated. It was observed that the S-layer alone was able to mediate haemagglutination. In adherent and invasive studies, transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
88
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 64 publications
(41 reference statements)
3
88
0
Order By: Relevance
“…Some previous studies suggested that T. forsythia and C. rectus possessed an S-layer on the cell surface, which has been associated with virulence in periodontitis 5,16) . Monitoring of these bacteria may prove to be an important tool in periodontal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies suggested that T. forsythia and C. rectus possessed an S-layer on the cell surface, which has been associated with virulence in periodontitis 5,16) . Monitoring of these bacteria may prove to be an important tool in periodontal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible explanation is that other bacterial components involved in invasion might also contribute to PI3K activation. Although the identity of these components is currently unknown, an earlier study has demonstrated that T. forsythia S-layer proteins also mediate attachment to and invasion of KB epithelial cells (Sabet et al, 2003). Interestingly, T. forsythia whole cells and their components have been shown to activate the pattern recognition receptor Toll-like receptor (TLR)2 (Hasebe et al, 2004;Kikkert et al, 2007;Onishi et al, 2008), and PI3K is also a downstream target of TLR2 activation.…”
Section: Tyrosine Kinase(s) and Pi3k Are Involved In T Forsythia Invmentioning
confidence: 99%
“…T. forsythia has been detected intracellularly in buccal and crevicular epithelium of patients with periodontitis (Colombo et al, 2007;Rudney et al, 2005). Furthermore, T. forsythia has been shown to invade epithelial cells in vitro (Han et al, 2000;Inagaki et al, 2006;Kirschbaum et al, 2010;Sabet et al, 2003). Thus, it is likely that this bacterium exploits epithelial cell invasion to avoid host defence surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…(Higuchi et al, 2000;Moriguchi et al, 2003). Sabet et al (2003) reported that the S-layer consists of 200 and 210-kDa proteins. In their study, the bacterial cells were resuspended in 0.1 M cacodylate buffer with 1% glutaraldehyde, and post fixed with 1% OsO 4 .…”
mentioning
confidence: 99%